Changes in microbial community during hydrolyzed sludge reduction - Liu, Shaomin; Wu, Jiating; Hu, Ziyan; Jiang, Mengyu (Frontiers in Microbiology, 2023)
In this study, the effects of different enzymes (lysozyme, α-amylase and neutral protease) on sludge hydrolysis efficiency and microbial community in sequencing batch reactor (SBR) were introduced. The results showed that the hydrolysis efficiencies of the three enzymes were 48.5%, 22.5% and 31%, respectively, compared with the accumulated sludge discharge of the blank control group. However, it has varying degrees of impact on the effluent quality, and the denitrification and phosphorus removal effect of the system deteriorates. The lysozyme that achieves the optimal sludge hydrolysis effect of 48.5% has the greatest impact on the chemical oxygen demand (COD), total nitrogen (TN), and nitrate nitrogen (NO3 –N) of the effluent. The sludge samples of the control group and the groups supplemented with different enzyme preparations were subjected to high-throughput sequencing. It was found that the number of OTUs (Operational Taxonomic Units) of the samples was lysozyme > α-amylase > blank control > neutral protease. Moreover, the abundance grade curve of the sludge samples supplemented with lysozyme and α-amylase was smoother, and the community richness and diversity were improved by lysozyme and α-amylase. The species diversity of the sludge supplemented with lysozyme and neutral protease was great, and the community succession was obvious. The introduction of enzymes did not change the main microbial communities of the sludge, which were mainly Proteobacteria, Actinobacteria and Bacteroidetes. The effects of three enzyme preparations on sludge reduction and microbial diversity during pilot operation were analyzed, the gap in microbial research was filled, which provided theoretical value for the practical operation of enzymatic sludge reduction.